Preferensi Pengguna Gang Terhadap Peletakan Signage Sebagai Respons Terhadap Pandemi COVID-19 di Kampung Sekayu Kota Semarang - Paskalis Noventus Krishartadi; Novia Sari Ristianti (Jurusan Perencanaan Wilayah dan Kota, 2023)
Public spaces need to adapt to the COVID-19 pandemic by supporting the implementation of health protocols, so they do not become places for the virus to spread. Alleys in urban kampung as public spaces are undoubtedly prone to spread the virus. The narrow width of the alley makes it difficult for people to implement health protocols like the alleys in Kampung Sekayu in Semarang, which have not shown any adaptation. Signage has not been used to remind the implementation of health protocols. The research aims to find and recognize the placement of signage elements to help the implementation of health protocols in the alleys in Kampung Sekayu. This research method is quantitative with quantitative descriptive analysis techniques. The results of this study are directional signage is placed on the side of the alleyway adjacent to the fence of the surrounding house, identification and information signage are placed on the side of the alleyway which is not adjacent to the fence of the surrounding house. Directional signage is placed on the inside of the alley intersection, identification and information signage are placed on the outside of the alley intersection.